(untitled) (Praxis Educativa, 2022)
This article presents the results of a research whose general objective was to contribute to the understanding of the transformations in the student experiences of the first year in times of forced virtualization. The axes of inquiry were the perceptions about the support received and the relationship with teachers, the valuations of the educational relationship and the imaginaries about the first year of students from three Faculties of the National University of Rosario. The research was framed in a mixed methodological paradigm and used the questionnaire as a data collection technique. Among the main findings we can mention the positive evaluation of the students regarding the accompaniment received and the bond established with their teachers, an accentuation of the students’ expectations regarding the pedagogical bond around issues of care and great transformations in the student experience that implied new difficulties in the processes of institutional and intellectual affiliation.